Who made the world's largest green tide in China?—an integrated study on the initiation and early development of the green tide in Yellow Sea. (6th April 2015) - Wang, Zongling; Xiao, Jie; Fan, Shiliang; Li, Yan; Liu, Xiangqing; Liu, Dongyan
Abstract To discover the original source and clarify development of the world's largest transregional green tides in the Yellow Sea, an integrated investigation covering the Subei Shoal coastal waters and the adjacent regions was carried out during March to June of 2012. The results showed that macroalgal wastes from the connecting ropes of Porphyra aquaculture rafts contributed significantly to the original biomass of free‐floating green algae. Approximately 6500 t of Ulva prolifera were released into the coastal waters from mid‐April to late‐May when farmers were cleaning aquaculture facilities. Among the total biomass disposed, about 62.3% floated up to the sea surface, which turned into the original floating patches. The floating U. prolifera, with a high growth rate of 26.3% per day, dominated in the floating algal patches rapidly, moved northward under the hydrodynamic action, and formed a massive free‐floating green tide near the south of Shandong peninsula in early June. The optimal sea temperature and sufficient nutrients in the Yellow Sea facilitated the formation of the green tide. No other source contributing substantially to the initial floating biomass was detected in the survey except those from the connecting ropes of rafts. Based on our field data, we concluded that the green tide in Yellow Sea is a transregional disaster stimulated directly by the unhygienic husbandry and maintenance practices of coastal aquaculture.